A Review of Mobile Banking Adoption Factors by Customers for Iraqi Banks - Nawar Makttoof, MR.; Haliyana Khalid, Dr. (International Journal of Engineering and Technology, 2018)
Mobile banking is becoming the delivery of self-service channel that helps banks to present information and also offer solutions to their own clients with more convenience via the internet services technology. This paper presents a review of mobile banking implementations all over the world in addition to reports on findings such as issues and benefits and associated with mobile banking adoption. However, the adoption of this complex innovation is a complicated task as discussed by the literature; thus, careful consideration and planning to all crucial factors that affect the adoption process through users is required. The aim of this study is to evaluate the factors that influence the adoption of mobile banking frameworks in banks industry. The study was performed utilizing a non-experimental study exploratory research design. This exploratory study included an essential investigation about secondary data. The study development and modeling of secondary data in order to highlight the final results of the research. Through reviewing the literature of the existing frameworks in mobile banking adoption, it is showed that the banks in Iraq needs continued attention to get government support, Iraqi mobile banking services have limited developed over the latest years in the different levels of banks and mobile services.Â Â